An Evaluation of Risk Attitudes and Risk Tolerance in Emergency Medicine Residents - Rodriguez, Carlos (Cureus, 2019)
Introduction Previous studies have shown that risk attitudes and tolerance for uncertainty are significant factors in clinical decision-making, particularly in the practice of defensive medicine. These attributes have also been linked with rates of physician burnout. To date, the risk profile of emergency medicine (EM) physicians has not yet been described. Our goal was to examine the risk profile of EM residents using a widely available risk tolerance and attitude assessment tool. Methods First-, second-, and third-year residents of Thomas Jefferson University Hospital’s EM residency program completed the commercially available, unmodified Risk Type Compass, a validated instrument offered by Multi-Health Systems (MHS Inc, New York, USA). Scored reports included information on residents’ risk type (one of eight personality types that reflect their temperament and disposition); risk attitudes (domains where residents are more likely to engage in risky behaviors); and an overall risk tolerance indicator (RTi) (a numerical estimate of risk tolerance). RTi scores are reported as means with 95% confidence intervals (CIs). Results There was no significant change in RTi scores in residents across different years of their post-graduate year (PGY) training. PGY-one residents trended towards risk aversion; PGY-two residents were more risk-taking; and PGY-three residents scored in the middle. Conclusion Our pilot assessment of risk types in EM residents highlighted shifts across the years of training. Variations between members of each PGY cohort outweighed any outright differences between classes with regards to absolute risk tolerance. There was an increase in the frequency of health and safety risk-taking attitude with higher PGY class, and this was also the risk attitude that was the prominent domain for resident risk tolerance. The study was limited by sample size and single cross-sectional evaluation.